The Value of Brain Imaging and Electrophysiological Testing for Early Screening of Autism Spectrum Disorder: A Systematic Review - Clairmont, Cullen; Wang, Jiuju; Tariq, Samia; Sherman, Hannah Tayla; Zhao, Mingxuan; Kong, Xue-Jun (Frontiers in Neuroscience, 2022)
Given the significance of identifying reliable biomarkers for the early detection of autism spectrum disorder (ASD), this systematic review aims to summarize available evidence of neuroimaging and neurophysiological changes in high-risk children to improve ASD early diagnosis. We included all peer-reviewed primary research in English published before May 21, 2021, involving the use of MRI, EEG, or fNIRS in children with high risk for ASD under 24 months of age. The main exclusion criteria includes diagnosis of a genetic disorder and gestation age of less the 36 weeks. Online research was performed on PubMed, Web of Science, PsycINFO, and CINHAL. Article selection was conducted by two reviewers to minimize bias. This research was funded by a Massachusetts General Hospital Sundry funding. IRB approval was not submitted as it was deemed unnecessary. We included 75 primary research articles. Studies showed that high-risk infants had divergent developmental trajectories for fractional anisotropy and regional brain volumes, increased CSF volume, and global connectivity abnormalities on MRI, decreased sensitivity for familiar faces, atypical lateralization during facial and auditory processing, and different spectral powers across multiple band frequencies on EEG and distinct developmental trajectories and regional oxyhemoglobin concentrations in fNIRS. These findings in infants were found to be correlated with the core ASD symptoms and diagnosis at toddler age. Despite the lack of quantitative analysis of the research database, neuroimaging and electrophysiological biomarkers have promising values for the screening of ASD as early as infancy with high accuracy, which warrants further investigation.